Upotreba lokativa u romanima Mihaila Lalića - Jovović, Nataša (Slavistična revija, 2015)
The paper examines the meaning and function of locative phrases in the novelistic opus of Mihailo Lalić, including all creative stages of this author: Svadba (1950, 1973), Raskid (1955, 1969), Lelejska gora (1957, 1983), Ratna s reća (1973, 1983), and Tamara (1992). Given the fact that syntax is characterized by methodological pluralism, in addition to the method of induction and deduction, the author in this paper also employs the basic syntactic methodology consisting of the synthetic procedure, i.e., of generation and analysis (parsing or segmentation). In this process the (un)markedness of locative constructions as well as their semantic content are taken into consideration.
Keywords: case; črnogorski pisatelji; Lalić, Mihajlo, 1914-1992; locative; Montenegrin writers; skladnja; sklon; srbščina; stilistika; stylistics; syntax